2018
DOI: 10.1097/mnm.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of normal spinal osseous metabolism with 18F-NaF PET/CT

Abstract: We assessed the metabolic activity of the spine's osseous tissues with F-NaF PET using a global assessment approach in healthy men. Our study provides evidence of differences in spinal metabolism as related to weight, but not age. Our study offers a foundation for future larger studies in symptomatic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…In the regional image quality assessment, the skull, thoracic and lumbar spine, and proximal long bones were scored excellent and acceptable, with the thoracic and lumbar spine scoring the highest on image quality. This finding is consistent with a study in skeletally immature healthy canines ( 53 ), and a human study of the spine with [ 18 F]NaF in healthy individuals were thoracic and lumbar spine had significant higher uptake compared to the cervical spine ( 54 ). An intriguing finding of the current study was that the cervical spine images were scored excellent and acceptable for most of the samples (96%) and 4% were scored insufficient.…”
Section: Discussionsupporting
confidence: 91%
“…In the regional image quality assessment, the skull, thoracic and lumbar spine, and proximal long bones were scored excellent and acceptable, with the thoracic and lumbar spine scoring the highest on image quality. This finding is consistent with a study in skeletally immature healthy canines ( 53 ), and a human study of the spine with [ 18 F]NaF in healthy individuals were thoracic and lumbar spine had significant higher uptake compared to the cervical spine ( 54 ). An intriguing finding of the current study was that the cervical spine images were scored excellent and acceptable for most of the samples (96%) and 4% were scored insufficient.…”
Section: Discussionsupporting
confidence: 91%
“…59 Although the thorough analysis of blood flow, metabolic rate, bone turnover, the pharmacokinetics of [ 18 F]NaF provides more information in the assessment of osteoporosis, the quantitative analysis of ROIs by SUVmean is a more simple and convenient way to obtain valuable results. 60 In the present study, RNA sequencing results showed that the expression of Col10a1 and Col2a1 genes were upregulated in the bone tissues of the mice treated with WJ-MSC-EVs, and both genes have key roles in entochondrostosis. 61 During chondrocyte maturation, Col10a1 is specifically expressed by hypertrophic chondrocytes in the hypertrophic zone of the growth plate, whereas the mutation of Col10a1 might cause growth plate defects and skeletal disorders.…”
Section: Discussionsupporting
confidence: 50%
“… 59 Although the thorough analysis of blood flow, metabolic rate, bone turnover, the pharmacokinetics of [ 18 F]NaF provides more information in the assessment of osteoporosis, the quantitative analysis of ROIs by SUVmean is a more simple and convenient way to obtain valuable results. 60 …”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82] The observation that NaF uptake at the cervical, thoracic, and lumbar spine is associated with increased body weight in healthy individuals suggests that NaF-PET/CT can detect early changes in the spine related to degeneration. 83 In 42 adult patients with back pain and no history of spine surgery, NaF-PET/CT scans identified the cause of pain in 37 (88%) of the patients. 82 Furthermore, NaF activity at lumbar facet joints has been found to correlate with both MR findings and clinical disability.…”
Section: Back Painmentioning
confidence: 99%